Pengembangan Game Edukasi Fisika Berbasis Matlab pada Pokok Bahasan Kinematika - Siwi Puji Astuti; Nurullaeli Nurullaeli; Alpi Mahisha Nugraha (SAP (Susunan Artikel Pendidikan), 2023)
Educational games can be designed using technological assistance so that in terms of appearance, they become more attractive for use in supporting the learning process. There are 2 types of educational games, namely online games and offline games, depending on the goals and objectives to be achieved. The use of educational games on kinematics material is used to help students prefer kinematics material so that student understanding can be improved. The purpose of this study was to determine the feasibility of a Matlab-based physics educational game on the subject of kinematics. The research was conducted in an odd semester of the 2022/2023 academic year, while the subjects of this research were 3rd semester students of the Informatics Engineering Study Program, Indraprasta University PGRI. The research used is research development (R&D) or often also called Research & Development. R&D is a scientific way to produce a product and validate the product. The development model used is ADDIE (Analysis, Design, Development, Implementation and Evaluation). The development of a physics educational game that has been made using Matlab on the subject of kinematics has been tested for its feasibility. Based on the results of the validation feasibility test calculations by material experts, media experts, and students, a feasibility value of 86.88% was obtained in the good category so that the development of Matlab-based physics education games is feasible to be used as a companion in learning activities.